2018
DOI: 10.1515/libri-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Acceptance of Mobile Library Applications: Structural Equation Model

Abstract: Acceptance and intention to use mobile applications in a library context is attracting a great deal of interest in education field. A sparse amount of research was conducted in mobile library applications (MLA) previously, investigating the influential factors of intention to use MLA. Research here aims to provide empirical support on acceptance of MLA, library access through mobile applications, with the model developed by taking a technology acceptance model (TAM) in MLA context by adding perceived mobility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 32 publications
7
49
1
3
Order By: Relevance
“… 38 2018 Exploring undergraduate students' usage pattern of mobile apps for education Journal of Librarianship and Information Science Wai, I.S.H., Ng, S.S.Y., Chiu, D.K.W., Ho, K.K.W., Lo, P. 39 2018 An empirical study on customer adoption of mobile payment application in India International Journal of Enterprise Network Management Joseph, J., Sriram, K.V., Rodrigues, L.L.R., Mathew, A.O., Gana, K.C. 40 2018 Willingness to pay and disposition toward paying for apps: The influence of application reviews International Journal of E-Services and Mobile Applications Furner, C.P., Zinko, R.A. 41 2018 What drives users' intentions to purchase a GPS Navigation app: The moderating role of perceived availability of free substitutes Internet Research Wang, Y.-Y., Lin, H.-H., Wang, Y.-S., Shih, Y.-W., Wang, S.-T. 42 2018 Users' acceptance of innovative mobile hotel booking trends: UK vs. PRC Information Technology and Tourism Tao, M., Nawaz, M.Z., Nawaz, S., Butt, A.H., Ahmad, H. 43 2018 A focus group study observing maternal intention to use a WIC education app American Journal of Health Behavior Friedman, B.L., Silva, M., Smith, K. 44 2018 Factors affecting acceptance of mobile library applications: Structural equation model Libri Rafique, H., Anwer, F., Shamim, A., (…), Qureshi, M.A., Shamshirband, S. 45 2018 A bidirectional perspective of trust and risk in determining factors that influence mobile app installation International Journal of Information Management Chin, A.G., Harris, M.A., Brookshire, R. …”
Section: Methodsmentioning
confidence: 99%
“… 38 2018 Exploring undergraduate students' usage pattern of mobile apps for education Journal of Librarianship and Information Science Wai, I.S.H., Ng, S.S.Y., Chiu, D.K.W., Ho, K.K.W., Lo, P. 39 2018 An empirical study on customer adoption of mobile payment application in India International Journal of Enterprise Network Management Joseph, J., Sriram, K.V., Rodrigues, L.L.R., Mathew, A.O., Gana, K.C. 40 2018 Willingness to pay and disposition toward paying for apps: The influence of application reviews International Journal of E-Services and Mobile Applications Furner, C.P., Zinko, R.A. 41 2018 What drives users' intentions to purchase a GPS Navigation app: The moderating role of perceived availability of free substitutes Internet Research Wang, Y.-Y., Lin, H.-H., Wang, Y.-S., Shih, Y.-W., Wang, S.-T. 42 2018 Users' acceptance of innovative mobile hotel booking trends: UK vs. PRC Information Technology and Tourism Tao, M., Nawaz, M.Z., Nawaz, S., Butt, A.H., Ahmad, H. 43 2018 A focus group study observing maternal intention to use a WIC education app American Journal of Health Behavior Friedman, B.L., Silva, M., Smith, K. 44 2018 Factors affecting acceptance of mobile library applications: Structural equation model Libri Rafique, H., Anwer, F., Shamim, A., (…), Qureshi, M.A., Shamshirband, S. 45 2018 A bidirectional perspective of trust and risk in determining factors that influence mobile app installation International Journal of Information Management Chin, A.G., Harris, M.A., Brookshire, R. …”
Section: Methodsmentioning
confidence: 99%
“…In the city, vehicle may travel slower than outside the city, at early morning traveling speed may be different from office timings. Also, vehicle speeds are dependent on traffic density, and depending on driver's behavior speed may vary too [32] [33]. By keeping this in consideration and to make it closer to reality variable speeds are assigned to vehicles ranging from 30KM/h to 70KM/h in 10KM/h chunks.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, the measurement model shows the association among the latent variable and the data gathered from the survey [102]. SEM assists in evaluating the association between endogenous and exogenous variables at once rather than doing it separately [103]. In this study, the sample size used was exceeding the suggested size of the sample, i.e.…”
Section: ) Participantsmentioning
confidence: 99%